Association of Dendritic Cell Signatures With Autoimmune Inflammation Revealed by Single‐Cell Profiling. Issue 5 (6th April 2019) - Ashton, Michelle P.; Eugster, Anne; Dietz, Sevina; Loebel, Doreen; Lindner, Annett; Kuehn, Denise; Taranko, Anna E.; Heschel, Babett; Gavrisan, Anita; Ziegler, Anette‐Gabriele; Aringer, Martin; Bonifacio, Ezio
Abstract : Objective: To identify single‐cell transcriptional signatures of dendritic cells (DCs) that are associated with autoimmunity, and determine whether those DC signatures are correlated with the clinical heterogeneity of autoimmune disease. Methods: Blood‐derived DCs were single‐cell sorted from the peripheral blood of patients with rheumatoid arthritis, systemic lupus erythematosus, or type 1 diabetes as well as healthy individuals. DCs were analyzed using single‐cell gene expression assays, performed immediately after isolation or after in vitro stimulation of the cells. In addition, protein expression was measured using fluorescence‐activated cell sorting. Results: CD1c+ conventional DCs and plasmacytoid DCs from healthy individuals exhibited diverse transcriptional signatures, while the DC transcriptional signatures in patients with autoimmune disease were altered. In particular, distinct DC clusters, characterized by up‐regulation of TAP1, IRF7, and IFNAR1, were abundant in patients with systemic autoimmune disease, whereas DCs from patients with type 1 diabetes had decreased expression of the regulatory genes PTPN6, TGFB, and TYROBP . The frequency of CD1c+ conventional DCs that expressed a systemic autoimmune profile directly correlated with the extent of disease activity in patients with rheumatoid arthritis (Spearman's r = 0.60, P = 0.03). Conclusion: DC transcriptional signatures are altered in patients with autoimmune disease and are associated with the level of disease activity, suggesting that immune cell transcriptional profiling could improve our ability to detect and understand the heterogeneity of these diseases, and could guide treatment choices in patients with a complex autoimmune disease.